2019
DOI: 10.3389/fpsyg.2019.02834
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Autonomy Support in Physical Education Classes as a Predictor of Motivation and Concentration in Mexican Students

Abstract: There is a strong belief that physical education can affect an individual's physical activity, healthy habits, and behaviors through pleasant, positive, and significant exercise experiences, a practical knowledge base, and comprehensive teaching strategies. However, a crucial cognitive aspect for the effective and significant learning of the activities offered in the educational environment is the concentration of students. This study aims to test a hypothetical model based on self-determination theory to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
1
13
0
3
Order By: Relevance
“…According to the SDT, it is known that PAS in class leads to students' psychological changes, which, in turn, affects students' engagement in learning (Burkley & Burkley, 2018). Also, some studies have shown that secondary school students' PAS significantly affects LM and SE (Jang et al, 2009;Maldonado et al, 2019;Ryan & Patrick, 2001). In addition, Ryan and Deci (2020) indicated that the high LM of students could promote their engagement and academic performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the SDT, it is known that PAS in class leads to students' psychological changes, which, in turn, affects students' engagement in learning (Burkley & Burkley, 2018). Also, some studies have shown that secondary school students' PAS significantly affects LM and SE (Jang et al, 2009;Maldonado et al, 2019;Ryan & Patrick, 2001). In addition, Ryan and Deci (2020) indicated that the high LM of students could promote their engagement and academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Students' satisfaction with autonomy support increases engagement in learning, intrinsic motivation, skill development, academic achievement, vitality, and well-being (Reeve & Cheon, 2021). In recent years, PAS has drawn scholars' attention (Black & Deci, 2000;Maldonado et al, 2019;Reeve & Cheon, 2021) with past study having found that PAS significantly impacts SE (Fredricks et al, 2019;Jang et al, 2010;Li, 2020;Wang et al, 2017). Gutiérrez and Tomás (2019) suggested that college students' PAS had a significant direct influence on SE, which predicted school satisfaction and academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…SDT postulates that for optimal well-being and autonomous motivation, three basic psychological needs must be met—autonomy (the feeling that behaviour is volitional and self-directed), relatedness (a sense of belonging and connectedness to others) and competence (perceived capability of maintaining and enhancing current skills and achieving desired objectives) [ 34 ]. Past research has shown that adolescent PA can be improved when these basic needs are met [ 35 , 36 ], thus the HERizon Project intervention was developed utilising the SDT framework.…”
Section: Introductionmentioning
confidence: 99%
“…
Introduction28 The ability to be attentive has been widely regarded as a major prerequisite in motor learning 29 (Wulf & Lewthwaite, 2016), whether in a sport (Moran, 2016) or an educational context 30 where physical activities are taught (Standage et al, 2005). However, sport participants can 31 experience difficulties in turning their attention on sport situation (Maldonado et al, 2019; 32 Moran, 2016). Less is known on how to optimize attention during a sport situation.
…”
mentioning
confidence: 99%
“…Moran, 49 2016) and physical education (PE; e.g. Maldonado et al, 2019). In contrast, distraction was 50 defined as a diversion of attention from some intended targets (Moran, 2016).…”
mentioning
confidence: 99%